2022
DOI: 10.3390/nu14214527
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Avoidant/Restrictive Food Intake Disorder among 2–10-Year-Old Children: The Significance of Maternal Feeding Style and Maternal Eating Disorders

Abstract: The aim of the present study was to investigate whether the feeding style and core behavioral features of eating disorders of mothers are related to the symptoms of Avoidant/Restrictive Food Intake Disorder (ARFID) among their children. This study involved 207 mothers of children aged 2 to 10 years (Mage = 5.82 ± 2.59 years), of which 19.32% were children with neurodevelopmental disorders and 22.71% were children with chronic diseases (e.g., allergy, asthma, diabetes). The mothers were asked to complete the AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Those authors suggested that dietary patterns in infancy may set the foundation for lifelong eating patterns and possible eating problems [14]. Brytek-Matera et al showed that both the maternal feeding style and core behavioral features of eating disorders were associated with avoidant/restrictive food intake disorder symptoms among 2-to 10-year-old children [15].…”
Section: Discussionmentioning
confidence: 99%
“…Those authors suggested that dietary patterns in infancy may set the foundation for lifelong eating patterns and possible eating problems [14]. Brytek-Matera et al showed that both the maternal feeding style and core behavioral features of eating disorders were associated with avoidant/restrictive food intake disorder symptoms among 2-to 10-year-old children [15].…”
Section: Discussionmentioning
confidence: 99%
“…In response to these challenges, the Special Issue presented a collection of research papers and reviews that explored various dimensions of parent–child interactions [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Among the highlighted studies was an investigation into the effects of Focal Play Therapy with Children and Parents, which revealed significant improvements in parent–child interactions post-intervention.…”
mentioning
confidence: 99%
“…Feeding difficulties are associated with both permissive and authoritarian parenting style (4). Anxiety, depression, stress, and behavioral features of eating disorders in mothers can affect behaviors in the feeding situation (5,6). Maternal depression is related to slow weight gain in infants (7).…”
mentioning
confidence: 99%